2006
DOI: 10.3171/spi.2006.5.6.543
|View full text |Cite
|
Sign up to set email alerts
|

Pseudoglandular schwannoma of the cauda equina

Abstract: The authors present a case of pseudoglandular schwannoma with immunohistochemical findings consistent with epithelial metaplasia. Pseudoglandular schwannoma is a rare morphological variant of benign schwannoma characterized by the presence of glandlike structures lined with Schwann cells. To the best of the authors' knowledge, this is only the fifth case of pseudoglandular schwannoma reported in the literature. Clinical, imaging, and pathological findings are described. The pathological findings were consisten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The significance of inflammation in most schwannomas is unclear, but in vestibular schwannomas, the presence of CD163‐positive macrophages has been correlated with vascular density and tumor growth . Schwannomas may show areas with an epithelioid morphology (Figure H), and some subcutaneous examples are predominantly epithelioid , but true epithelial metaplasia is rare . A rare variant of schwannoma contains areas of neuroblastoma‐like rosettes, but this should not be confused with malignant neuroectodermal tumors .…”
Section: Pathologymentioning
confidence: 99%
“…The significance of inflammation in most schwannomas is unclear, but in vestibular schwannomas, the presence of CD163‐positive macrophages has been correlated with vascular density and tumor growth . Schwannomas may show areas with an epithelioid morphology (Figure H), and some subcutaneous examples are predominantly epithelioid , but true epithelial metaplasia is rare . A rare variant of schwannoma contains areas of neuroblastoma‐like rosettes, but this should not be confused with malignant neuroectodermal tumors .…”
Section: Pathologymentioning
confidence: 99%
“…Cells that form pseudoglandular structures undergo "epithelial metaplasia". In the case report by Ruggeri [5], the findings of focal epithelial membrane (EMA) and cytokeratin positivity in pseudoglandular areas support this theory. It also been reported that pseudoglandular schwannoma may progress to glandular schwannoma [6,7].…”
Section: Discussionmentioning
confidence: 82%